MOLECULAR DIFFERENTIATION OF MITOCHONDRIAL GLYCEROL-3-PHOSPHATE ACYLTRANSFERASE AMONG DIFFERENT BREEDS OF BUBALUS BUBALIS - ANIL KUMAR,; VINOD CHHOKAR,; RAVINDER KUMAR,; VIKAS BENIWAL,; S. N. KALA,; ANAMIKA MISHRA,; P. K. NAIK, (International Journal of Pharma and Bio Sciences, 2012)
Mitochondrial Glycerol-3-phosphate acyltransferase (GPAM; EC 2.3.1.15), catalyzes the first step of glycerolipid biosynthesis. It plays a key role in the regulation of cellular triacylglycerol and phospholipid levels. The GPAM esterification step constitutes the committed reaction in the de novo synthesis of triacylglycerol (TAG) and all the acyl-glycerol phospholipids. In the present investigation GPAM was partially amplified (around 652 bp) by designing gene specific primers and confirmed by sequencing the amplicon and its comparison with the GPAM gene of bovine. Comparative study of GPAM among different breeds of buffaloes reveals different level of mutations with respect to its gene sequence 2.7-5.6% and protein sequence 3.4% to 13%. Similarly the protein structures modeled from their sequences were compared by structural superposition that shows variations (Root Mean Square Deviation) from 0.26 to 1.025. Molecular differentiation among different breeds of buffaloes reveals that the reference and Bhadawari are very close to each other, Toda and Surti are similarly close to each other and Pandharpuri is related to Murrah. Especially the variations are more at the binding site of this protein that may be the cause that different breeds have different percentage of milk fat. Further study is underway to detect polymorphism and associate them with milk fat related traits in buffalo.